Political boundary making toward Poland: Social identities and interest-formation in German elite reasoning - Matthias Ecker (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1999)
Using data from the `German-Polish Elite Study', the paper presents findings as to how the German `positional elite' thinks about the changing political significance of the border between Germans and Poles. Three dimensions of current `political boundary making' are considered: Restrictions on cross-border traffic at Oder and Neisse and the two enlargements of the European Union and NATO respectively. As can be shown, while `transnational' identity ties between German and Polish elite members foster support for political integration, national identification is in some ways still an obstacle to `de-bordering'. Nevertheless, interests – although themselves depending on social identities – are still (more) important variables for understanding how boundaries are drawn. With respect to enlargements, the German elites support a reduction in the political signifi-cance of the German-Polish border; albeit more in terms of a European `society' based on functional regimes like EU and NATO than a European `community' in the sociological meaning. With respect to controls: while borders may vanish as military `hard shells' (John Herz), the German-Polish state border is still seen as a necessary instrument against crime, although with the `odour of a lost battle' in terms of efficacy. – – Mit Hilfe von Umfragedaten aus der “Deutsch-Polnischen Elitestudie” geht das discus-sion paper der Frage nach, wie die deutsche “Positionselite” über den Wandel der Grenze zwischen Deutschen und Polen denkt. Drei Dimensionen aktueller ,,politischer Grenzziehungen“ werden diskutiert: Restriktionen des grenzüberschreitenden Verkehrs an Oder und Neiße sowie die Integration Polens in die Europäische Union und die NATO. Es wird unter anderem gezeigt, daß zwar ,,transnationale“ Verbundenheit zwischen deutschen und polnischen Eliten positive Einstellungen gegenüber einer politischen Integration Polens begünstigt, Gefühle nationaler Identität jedoch immer noch einer ,,Entgrenzung“ entgegenstehen. Allerdings: Interessen tragen – obgleich selbst abhängig von sozialen Identitäten – immer noch erheblich zum Verständnis von ,,Grenzziehungen“ bei. Was die Erweiterungen anbetrifft, scheint die deutsche Elite bereit, die Grenze zu Polen weitgehend aufzugeben; allerdings eher im Sinne einer ,europäischen Gesellschaft`, die sich auf funktionale Regime wie EU oder NATO gründet, als einer ,europäischen Gemeinschaft` im soziologischen Sinne. Im Hinblick auf Grenzkontrollen: mö-gen Grenzen auch ihre militärische Bedeutung als ,hard shells` (John Herz) verloren haben, als Instrument gegen Kriminalität scheint die deutsch-polnische Grenze nach wie vor als notwendig betrachtet zu werden, wenn auch mit einem Hauch von verlorener Schlacht, was ihre Effiktivität anbetrifft.
Keywords: 320